MEREKONSTRUKSI SAINS ASLI (INDIGENOUS SCIENCE) DALAM RANGKA MENGEMBANGKAN PENDIDIKAN SAINS BERBASIS BUDAYA LOKAL DI SEKOLAH :Studi Etnosains pada Masyarakat Penglipuran Bali - Suastra, I Wayan (2005)
The ethno science study attempts to find out indigenous science that is inherited in traditional community and to develop local culture-based science education programe in school. This study was done in Bali Panglipuran traditional community. Indigenous science data was collected by observation, participation, comprehensive interview and documentation. The data as well as the method were triangulated. The result from this study : 1) Panglipuran traditional community selectively accepts the foreign cultures without leafing aside indigenous culture inherited from Bayung Gede. 2) Indigenous science that exists in community is still in based of concrete experience through interaction between nature and social culture. 3) As viewed from Western science, indigenous science can be classified into two categories which are indigenous science that can be explained by Western science (12 topics) and indigenous science that has not been explained by Western science (1 topic). Implications of this study for science education in school are: 1) indigenous science (local culture) should be accommodated as illustration in science learning in school, particularly those that are related to daily life. 2) Science teaching in school can be considered as local culture transmission. It is recommended to local National Education Department to establish a science curricula committee that involves curricula experts subject matter from college and university, science teachers and people who know local culture.